Successful Teachers, Successful Students : Recruiting and Supporting Society’s Most Crucial Profession - Béteille, Tara; Evans, David K (World Bank, Washington, DC, 2022)
Successful teachers are likely to be the first role models that young people encounter outside the home. They teach content, make learning fun, shape students’ attitudes, exemplify empathy, teach teamwork and respect, and build student confidence in several ways. Effective teachers prepare students for a world where they must interact with others, adapt quickly to change, and where success will hinge on knowledge as well as attitudes and behavior. Helping young people develop these skills is a complex task, especially when many come from deprived backgrounds. It requires routine human interface with people who combine deep knowledge, a conviction that all students can succeed, and empathy. Successful teachers are irreplaceable in this task and will remain irreplaceable in the future. Coronavirus (COVID-19)-related school closures changed the nature of interactions between students and teachers around the world. While students in some school systems remained in regular contact with their teachers through technology-enabled classes and continued to learn, many did not. School closures will take place in the future, if not worldwide, then in individual countries for a variety of reasons. To be effective, teachers must also be able to use technology effectively to ensure learning beyond school walls, navigate unpredictable circumstances, and be flexible based on student needs. Teachers are successful when teacher policies are designed and implemented in a manner that attracts high-ability individuals, and prepares, supports and motivates them to become high performing teachers. This paper describes the vision and key principles guiding the world bank’s support to countries on teachers.